2013
DOI: 10.1097/sap.0b013e31827e5353
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cell-Enriched Fat Transfer to Conventional Fat Grafting after Aesthetic Procedures Using a Patient Satisfaction Survey

Abstract: Cell-enriched fat transfer to the face and body of aesthetic patients produces high satisfaction rates. Our preliminary data demonstrates similar satisfaction with regard to symmetry, scarring, and deformity in patients treated with CEFT versus AFT, without any complications. Unexpectedly, a clinical and statistical improvement in pigmentation was seen for patients treated with CEFT over AFT. Further studies need to be done to better understand this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…After fat grafting, there is a progressive improvement of the skin texture, elasticity, and color over a few months. [13][14][15] Therefore, adipose tissue seems to be not only a simple filler but also a dynamic filler with two types of different and supplementary effects, the volumetric effect and the regenerative effect. The physiologic mechanisms of these dynamic phenomena are still not completely elucidated.…”
mentioning
confidence: 99%
“…After fat grafting, there is a progressive improvement of the skin texture, elasticity, and color over a few months. [13][14][15] Therefore, adipose tissue seems to be not only a simple filler but also a dynamic filler with two types of different and supplementary effects, the volumetric effect and the regenerative effect. The physiologic mechanisms of these dynamic phenomena are still not completely elucidated.…”
mentioning
confidence: 99%
“…Mailey et al (37) reported similar results between CAL and unenhanced cases with regard to symmetry, scarring and deformity; however, they did report a significant increase in skin improvement in patients who underwent CAL. It is well known that volume loss in the upper one-third of the face contributes significantly to the look of aging (38).…”
Section: Discussionmentioning
confidence: 61%
“…More important is the fact that several studies neglected to specify the complications and only sufficed with the annotation that there were none. These studies 67 , 68 were therefore excluded, and this adds further to a possible reporting bias. Finally, the very definition of a complication of AFT in facial rejuvenation is a complicated matter and a clear consensus whether, for example, postoperative pain qualifies as a complication or part of the normal postoperative course is still lacking.…”
Section: Discussionmentioning
confidence: 99%